Total Laparoscopic Hysterectomy: Overtreatment for Misdiagnosed Organic cause or Undertreatment for Idiopathic Chronic Pelvic Pain?. Issue 4 (October 2014) - Gizzo, Salvatore; Leggieri, Concetta; Conte, Lorena; Luisi, Stefano; Zupi, Errico; Saccardi, Carlo; Litta, Pietro
Background: Chronic pelvic pain (CPP) is considered a symptom but also a syndrome with misunderstood pathophysiology and treatment options ranging from conservative management to opioid analgesia and surgical intervention. The aim of this study was to evaluate the role of gynecological surgery in modifying presurgical pain status and reducing the postoperative analgesic use of patients suffering CPP. The second aim of the study was to analyze intraoperative and histological differences in patients who benefited from surgery versus those without benefit. Methods: An observational study was conducted in 16 fertile women affected by CPP, treated by total laparoscopic hysterectomy (TLH) to solve their pelvic pain. In 7 cases, undetected pelvic endometriosis was found. Results: A complete resolution of pre-operative pain symptoms (score 0) occurred in 9 patients (56.2%), an occasional pelvic discomfort (score 1) in 2 cases (12.5%), 2 patients reported minimal benefit of pelvic pain (score 2), while in 3 cases, severe pain persisted (score 3). The correlation between intraoperative/histological features and reported symptoms after surgery showed that 7 of 9 patients (77.7%) who benefited from surgery were affected by an organic cause; while 5 women with minimal or no benefits from the surgery did not have any organic disease (idiopathic CPP). Conclusions: If conservative treatment fails to treat CPP, investigative laparoscopy represents a necessary step to discriminate patients with misdiagnosed organic from idiopathic CPP, selecting those who will potentially benefit from hysterectomy. The role of concomitant appendectomy needs to be defined in surgical treatment of idiopathic CPP.